Business communication - Raman, Meenakshi (Oxford University Press, 2006)
Business Communication is a comprehensive textbook that is specially designed to meet the needs of students pursuing Masters in Business Administration/Postgraduate Diploma in Management. Users will find this book highly useful for its coverage of decision-making for the business organization in relation to managerial communication, effective oral, written, and group communication skills, corporate communication, negotiation, and intercultural communication in business. The text is suitably interspersed through caselets, tables, and diagrams